Tema: “Implementación de programas de fungicidas más inductores de resistencia para el control de enfermedades de fruto en una plantación de cacao (Theobroma cacao L.), en el Cantón Montalvo, Provincia de Los Ríos - Burgos Andino, Ronald Gabriel (2016)
SUMMARY This research was carried out on the grounds of the "Mi Cielito" estate, owned by Mr. Javier Burgos Ortiz, located at Km 3.0 via Montalvo - Caluma, "La Lola Grande". It was located in a trinitarian cacao plantation clone CCN-51. The area has a humid tropical climate; With a height of 72 m.s.n.m., with geographic coordinates 79 ° 20' west longitude and 47 ° south latitude, an average rainfall of 1791.4 mm / year and with temperatures of 25.2 ° C. Disease presence data were evaluated; Damage assessment 48 hours prior to application; Incidence and severity of disease; Evaluation of control every 14 to 21 days after application; Percentage of decrease of damage; Leaf emission and yield per hectare As detailed above, it was determined that there was a greater presence of Monilia, in comparison to the disease of the Black Cob; The damage assessment was presented with higher averages when Triazol (0.4 L/ha) + Strobirulina (0.5 L/ha) + Morpholine (1.0 L/ha) was applied; The highest incidence and severity of the disease, both initial and final, as well as the highest percentage of affected tissue was observed in the absolute control (without application of products); (0.5 L/ha) + Strobirulin (0.5 L/ha) + Morpholine (1.0 L/ha) + Fyto 6 (0,15 L/ha).; Foliar emission was higher in treatments with Triazol (0.4 L/ha) + Cupric (0.5 L/ha) + Strobirulin (0.5 L/ha); Cupric (0.5 L/ha) + Strobirulin (0.5 L/ha) + Morpholine (1.0 L/ha); Trihydrate (0.4 L/ha) + Strobirulin (0.5 L/ha) + Morpholine (1.0 L/ha) and Fyto 6 (0,15 L/ha). and higher yield, as well as higher net benefit was obtained with the application of Cupric (0.5 L/ha) + Strobirulin (0.5 L/ha) + Morpholine (1.0 L/ha) + Fyto 6 (0,15 L/ha).